Wileński okres w życiu Iwo Jaworskiego - Koredczuk, Józef (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The Vilnius period in Iwo Jaworski’s life, from 1922 until 1939, was one of the most important periods in his life. It began when he became Chair of History of Law in Western Europe at the Stefan Batory University in 1922. It was also associated with the formation of the Faculty of Law and Social Sciences at the University. In 1927 Iwo Jaworski obtained his post-doctoral degree (habilitation) and in 1932 he was made professor. In his research he focused on political and legal questions connected with the French Revolution as well as legal questions concerning the Grand Duchy of Lithuania. In addition to conducting research, he was also active in popularising science, and was an outstanding teacher, whose lectures and seminars were very popular among students. That he was trusted by those around him is evidenced by his participation in several collegiate bodies at the university and the fact that he supervised several student organisations. The Vilnius period was also extremely important in his private life. It was in Vilnius that he started a family and despite the fact that he moved several times, his home was a place of social gatherings of many of his friends (including people who, like himself, found themselves in Wrocław after the war). Interludes in his life in Vilnius were provided by military training courses which he was called to attend.
Keywords: Jaworski Iwo (1898-1959); Uniwersytet Wileński; Wydział Prawa i Nauk Społecznych